Resin composition for ceramic green sheet, method for producing ceramic green sheet, and method for producing laminated ceramic electronic component

By using ceramic green sheet resin composition with ceramic powder and methylcyclohexane/ethanol mixed solvent, combined with other solvents, the problem of structural defects in laminated ceramic electronic components during the manufacturing process is solved, and the quality of the product is improved. reliability.

CN119183445APending Publication Date: 2024-12-24MURATA MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380040049.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-26
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

During the manufacturing process, existing stacked ceramic electronic components have structural defects such as peeling of the internal electrode layer and creating voids at the junction of the ceramic layer, which affects product quality.

Method used

The resin composition for ceramic green sheets using ceramic powder, polyvinyl butyral as the binder and a mixed solvent of methylcyclohexane/ethanol as the organic solvent is used to increase the plastic deformation of the ceramic green sheets by appropriate residual voids. Reduce structural defects during lamination and crimping, and add other solvents such as isopropanol, methyl ethyl ketone, etc. to the mixed solvent to improve the solubility of the adhesive.

Benefits of technology

It significantly reduces structural defects of stacked ceramic electronic components, improves product quality and reliability, and reduces short-circuit rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119183445A_ABST
    Figure CN119183445A_ABST
Patent Text Reader

Abstract

The resin composition for a ceramic green sheet according to the present invention contains a ceramic powder, a binder, and an organic solvent, the binder being polyvinyl butyral, and the organic solvent being a mixed solvent containing methylcyclohexane and ethanol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for a ceramic green sheet, a method for producing a ceramic green sheet, and a method for producing a laminated ceramic electronic component. Background Art

[0002] Laminated ceramic electronic components such as laminated ceramic capacitors are usually manufactured through the following process. First, a ceramic green sheet resin composition (ceramic slurry) dispersed with ceramic powder is prepared. Then, the ceramic green sheet resin composition is applied to a sheet and dried to make a ceramic green sheet. After forming an internal electrode pattern on the obtained ceramic green sheet, multiple ceramic green sheets with internal electrode patterns are stacked, and ceramic green sheets without internal electrode patterns are stacked on two main surfaces as needed to make a laminate. A ceramic sintered body is made by firing the obtained laminate. External electrodes are formed on the outer surface of the ceramic sintered body as needed. Through the above operations, a laminated ceramic electronic component can be obtained.

[0003] Patent Document 1 discloses a polyvinyl acetal resin having an average degree of polymerization of more than 4500 and less than 10000, an acetal group content of 45 to 80 mol%, a hydroxyl group content of 18 to 50 mol%, and an acetyl group content of 0.5 to 20 mol%. Patent Document 1 further discloses a ceramic green sheet composition containing the polyvinyl acetal resin and an organic solvent, a ceramic green sheet formed using the ceramic green sheet composition, and a laminated ceramic capacitor formed using the ceramic green sheet.

[0004] Patent document 2 discloses a method for manufacturing ceramic raw sheets, which is characterized by: a step of applying a coating slurry containing an organic solvent, ceramic powder and an organic resin binder into a sheet, and a step of continuously drying the slurry applied into a sheet in a drying furnace, and the above-mentioned drying step includes an initial drying step and a later drying step. In the above-mentioned initial drying step, the above-mentioned slurry applied into a sheet is dried until its organic solvent content becomes 20 to 40% by mass.

[0005] Patent document 3 discloses a method for manufacturing a ceramic green sheet, wherein a ceramic powder and an organic binder resin are mixed and dispersed in an organic solvent to obtain a ceramic slurry, and the ceramic green sheet is formed using the ceramic slurry. The method for manufacturing the ceramic green sheet is characterized in that: before mixing the ceramic powder, the ceramic powder is subjected to a humidification treatment so that the water content becomes 0.2 to 1.5% by weight. Furthermore, Patent document 3 discloses a method for manufacturing a laminated ceramic electronic component, characterized in that it includes the following steps: subjecting the ceramic powder to a humidification treatment so that the water content becomes 0.2 to 1.5% by weight; mixing the humidified ceramic powder and the organic binder resin in an organic solvent to obtain a ceramic slurry; using the ceramic slurry to form a sheet to obtain a ceramic green sheet; stacking a plurality of the ceramic green sheets with internal electrodes interposed therebetween to obtain a laminate; obtaining a ceramic sintered body by firing the obtained laminate; and forming an external electrode on the outer surface of the ceramic sintered body.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-56015

[0009] Patent Document 2: Japanese Patent Application Publication No. 2007-91526

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 11-348015 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the inventions described in Patent Documents 1 to 3 have room for improvement in manufacturing laminated ceramic electronic components with fewer structural defects, such as internal electrode layers peeling off from the ceramic layers and gaps being generated at the boundaries between the ends of the internal electrode layers and the ceramic layers.

[0013] The object of the present invention is to provide a ceramic green sheet resin composition that can obtain a laminated ceramic electronic component with reduced structural defects. Furthermore, the object of the present invention is to provide a method for producing a ceramic green sheet and a method for producing a laminated ceramic electronic component using the ceramic green sheet resin composition.

[0014] Means for solving problems

[0015] The resin composition for ceramic green sheets of the present invention comprises ceramic powder, a binder and an organic solvent. The binder is polyvinyl butyral and the organic solvent is a mixed solvent containing methylcyclohexane and ethanol.

[0016] The method for producing a ceramic green sheet of the present invention comprises the step of forming the resin composition for a ceramic green sheet of the present invention into a sheet shape.

[0017] The manufacturing method of the laminated ceramic electronic component of the present invention includes the following steps: preparing a ceramic green sheet by forming the resin composition for ceramic green sheets of the present invention into a sheet shape; forming an internal electrode pattern on the above-mentioned ceramic green sheet; preparing a laminate by stacking a plurality of the above-mentioned ceramic green sheets on which the above-mentioned internal electrode pattern is formed; and preparing a ceramic sintered body having a structure in which internal electrode layers are stacked with ceramic layers therebetween by firing the above-mentioned laminate.

[0018] Effects of the Invention

[0019] According to the present invention, a resin composition for ceramic green sheets can be provided, which can provide a laminated ceramic electronic component with reduced structural defects. Furthermore, according to the present invention, a method for producing ceramic green sheets and a method for producing a laminated ceramic electronic component using the above-mentioned resin composition for ceramic green sheets can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 FIG. 1 is a cross-sectional view schematically showing an example of a multilayer ceramic capacitor.

[0021] Figure 2 It is composed Figure 1 FIG. 1 is a cross-sectional view of a laminated body of a laminated ceramic capacitor taken along line II-II.

[0022] Figure 3 This is a cross-sectional view schematically showing an example of a structural defect in which a void is generated at the boundary between the end of the internal electrode layer and the ceramic layer.

[0023] Figure 4 This is a cross-sectional view schematically showing an example of a structural defect in which an internal electrode layer is peeled off from a ceramic layer. DETAILED DESCRIPTION

[0024] Hereinafter, the resin composition for ceramic green sheets of the present invention, the method for manufacturing ceramic green sheets and the method for manufacturing laminated ceramic electronic components are described. It should be noted that the present invention is not limited to the following structure, and appropriate changes can also be made within the scope of not changing the gist of the present invention. In addition, the scheme formed by combining a plurality of the preferred structures described below is also the present invention.

[0025] The drawings shown below are schematic diagrams, and their dimensions, aspect ratios, and other aspects may differ from those of actual products.

[0026] The resin composition for ceramic green sheets of the present invention contains ceramic powder, a binder and an organic solvent.

[0027] The resin composition for ceramic green sheets of the present invention is characterized in that the binder is polyvinyl butyral and the organic solvent is a mixed solvent containing methylcyclohexane and ethanol.

[0028] The ceramic green sheet resin composition of the present invention can be used to prepare a ceramic green sheet that can obtain high-quality chip components by using a mixed solvent containing methylcyclohexane and ethanol as an organic solvent. Specifically, by forming a ceramic green sheet with appropriate residual gaps, the plastic deformation of the ceramic green sheet can be increased, thereby reducing structural defects generated during the lamination and compression of the ceramic green sheet. As a result, a high-quality chip component can be obtained.

[0029] In the past, a toluene / ethanol mixed solvent was used as an organic solvent. It is believed that unlike a toluene / ethanol mixed solvent, a methylcyclohexane / ethanol mixed solvent has an azeotropic composition and a azeotropic point as low as 72°C (1 atmosphere) (78°C (1 atmosphere) for toluene / ethanol), so the volatility of the organic solvent is higher than in the past, and as a result, gaps remain appropriately in the ceramic green sheet. Furthermore, since methylcyclohexane is a solvent with a lower polarity than toluene, it is slightly less compatible with polyvinyl butyral used as a binder. As a result, a phase rich in methylcyclohexane is easily formed, and it is believed that this situation may also affect the size of the porosity of the ceramic green sheet.

[0030] In the resin composition for ceramic green sheets of the present invention, the mixed solvent preferably further contains at least one solvent selected from isopropyl alcohol, methyl ethyl ketone, methyl propyl ketone and methyl isobutyl ketone. By adding at least one of these solvents to the organic solvent, the solubility of polyvinyl butyral can be kept high even if the amount of methylcyclohexane added is increased. As a result, since the insolubility of polyvinyl butyral can be suppressed, the short circuit of the chip component can be reduced.

[0031] In the resin composition for ceramic green sheets of the present invention, the mixed solvent may further contain at least one solvent selected from isopropyl alcohol, methyl ethyl ketone, methyl propyl ketone and methyl isobutyl ketone, or may further contain two or more solvents. For example, in addition to containing methylcyclohexane and ethanol, the mixed solvent may also contain isopropyl alcohol and methyl ethyl ketone.

[0032] In the resin composition for ceramic green sheets of the present invention, the content of methylcyclohexane in the mixed solvent is not particularly limited, but if the content of methylcyclohexane is too small, it is difficult to obtain the effect of reducing structural defects, and on the other hand, if the content of methylcyclohexane is too large, it is difficult to prepare the resin composition. Taking these into consideration, the content of methylcyclohexane is preferably 20 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the total of methylcyclohexane and ethanol.

[0033] In the resin composition for ceramic green sheets of the present invention, the content of ethanol in the mixed solvent is not particularly limited, but is preferably 20 parts by weight or more and 80 parts by weight or less based on 100 parts by weight of the total of methylcyclohexane and ethanol.

[0034] In the resin composition for ceramic green sheets of the present invention, when the mixed solvent contains isopropyl alcohol, the content of methylcyclohexane is preferably 20 parts by weight to 80 parts by weight, and the content of isopropyl alcohol is preferably 0.4 parts by weight to 40 parts by weight, based on 100 parts by weight of the total of methylcyclohexane and ethanol.

[0035] In the resin composition for ceramic green sheets of the present invention, when the mixed solvent contains methyl ethyl ketone, the content of methylcyclohexane is preferably 20 parts by weight to 80 parts by weight, and the content of methyl ethyl ketone is preferably 0.4 parts by weight to 40 parts by weight, relative to 100 parts by weight of the total of methylcyclohexane and ethanol.

[0036] For example, in the case where the mixed solvent contains isopropyl alcohol and methyl ethyl ketone, the content of methylcyclohexane is preferably 20 parts by weight to 80 parts by weight, the content of isopropyl alcohol is preferably 0.4 parts by weight to 40 parts by weight, and the content of methyl ethyl ketone is preferably 0.4 parts by weight to 40 parts by weight, relative to 100 parts by weight of the total of methylcyclohexane and ethanol.

[0037] In the resin composition for ceramic green sheets of the present invention, when the mixed solvent contains methyl propyl ketone, the content of methyl cyclohexane is preferably 20 parts by weight to 80 parts by weight, and the content of methyl propyl ketone is preferably 0.4 parts by weight to 40 parts by weight, relative to 100 parts by weight of the total of methyl cyclohexane and ethanol.

[0038] In the resin composition for ceramic green sheets of the present invention, when the mixed solvent contains methyl isobutyl ketone, the content of methylcyclohexane is preferably 20 parts by weight to 80 parts by weight, and the content of methyl isobutyl ketone is preferably 0.4 parts by weight to 40 parts by weight, based on 100 parts by weight of the total of methylcyclohexane and ethanol.

[0039] In the resin composition for ceramic green sheets of the present invention, the mixed solvent may further contain toluene. However, if the content of toluene is too much, it is difficult to obtain the effect brought by methylcyclohexane, so when the mixed solvent contains toluene, the content of toluene is preferably 35 parts by weight or less relative to a total of 100 parts by weight of methylcyclohexane and ethanol. When the mixed solvent contains toluene, the content of toluene can be, for example, 20 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, 2 parts by weight or less, or 0.1 parts by weight or less relative to a total of 100 parts by weight of methylcyclohexane and ethanol.

[0040] In the resin composition for ceramic green sheets of the present invention, the mixed solvent preferably does not contain toluene. The expression "does not contain toluene" herein does not mean strictly not containing toluene, that is, only means the case where the toluene content is 0 parts by weight, but also means that it includes substantially no toluene, for example, contains toluene as an inevitable impurity.

[0041] In addition, the methylcyclohexane / ethanol mixed solvent contained in the ceramic green sheet resin composition of the present invention has solubility and erasability comparable to that of conventional toluene / ethanol mixed solvents in cleaning of equipment during dispersion or molding. Therefore, the mixed solvent contained in the ceramic green sheet resin composition of the present invention is also suitable for use as a cleaning liquid.

[0042] The method for producing a ceramic green sheet of the present invention comprises the step of forming the resin composition for a ceramic green sheet of the present invention into a sheet shape.

[0043] The ceramic green sheet can be produced by molding the resin composition for ceramic green sheets of the present invention into a sheet shape. Specifically, the ceramic green sheet can be produced by applying the resin composition for ceramic green sheets of the present invention into a sheet shape and then drying the sheet shape.

[0044] The manufacturing method of the laminated ceramic electronic component of the present invention includes the following steps: preparing a ceramic green sheet by forming the resin composition for ceramic green sheets of the present invention into a sheet shape; forming an internal electrode pattern on the above-mentioned ceramic green sheet; preparing a laminate by stacking a plurality of the above-mentioned ceramic green sheets on which the above-mentioned internal electrode pattern is formed; and preparing a ceramic sintered body having a structure in which internal electrode layers are stacked with ceramic layers therebetween by firing the above-mentioned laminate.

[0045] A multilayer ceramic electronic component such as a multilayer ceramic capacitor can be produced using a ceramic green sheet obtained by molding the resin composition for a ceramic green sheet of the present invention into a sheet shape.

[0046] Figure 1 FIG. 1 is a cross-sectional view schematically showing an example of a multilayer ceramic capacitor. Figure 2 It is composed Figure 1 FIG. 1 is a cross-sectional view of a laminated body of a laminated ceramic capacitor taken along line II-II.

[0047] exist Figure 1 The illustrated multilayer ceramic capacitor 1 includes a multilayer body 10 in which internal electrode layers 12 are stacked with ceramic layers 11 interposed therebetween. The internal electrode layers 12 are alternately exposed on the surface of the multilayer body 10 at end faces 15 and 16 of the multilayer body 10. In addition, a pair of external electrodes 13 and 14 electrically connected to the internal electrode layers 12 are formed on the end faces 15 and 16 of the multilayer body 10, respectively.

[0048] In the method for producing a laminated ceramic electronic component of the present invention, a laminate is produced by laminating a plurality of ceramic green sheets having internal electrode patterns. Figure 2 As shown, a plurality of ceramic green sheets having internal electrode patterns formed thereon are stacked to form an internal electrode holding layer 17 , and ceramic green sheets having no internal electrode patterns formed thereon are stacked on both main surfaces of the internal electrode holding layer 17 to form protective layers 18 and 19 , thereby manufacturing the laminate 10 .

[0049] By firing the obtained laminated body, a ceramic sintered body having a structure in which internal electrode layers are laminated with ceramic layers interposed therebetween is produced. External electrodes are formed on the outer surface of the ceramic sintered body as required. Through the above operation, laminated ceramic electronic components such as laminated ceramic capacitors can be obtained.

[0050] The following contents are disclosed in this specification.

[0051] <1>

[0052] A resin composition for ceramic green sheets, comprising ceramic powder, a binder and an organic solvent,

[0053] The above-mentioned adhesive is polyvinyl butyral,

[0054] The organic solvent is a mixed solvent containing methylcyclohexane and ethanol.

[0055] <2>

[0056] like <1> The resin composition for ceramic green sheets described above, wherein the mixed solvent further contains at least one solvent selected from the group consisting of isopropyl alcohol, methyl ethyl ketone, methyl propyl ketone and methyl isobutyl ketone.

[0057] <3>

[0058] like <1> or <2> The resin composition for ceramic green sheets described above, wherein the content of the methylcyclohexane is 20 parts by weight or more and 80 parts by weight or less based on 100 parts by weight of the total of the methylcyclohexane and the ethanol.

[0059] <4>

[0060] like <2> The resin composition for ceramic green sheets described herein, wherein the content of the methylcyclohexane is 20 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the total of the methylcyclohexane and the ethanol, and, when the mixed solvent contains the isopropyl alcohol, the content of the isopropyl alcohol is 0.4 parts by weight or more and 40 parts by weight or less, when the mixed solvent contains the methyl ethyl ketone, the content of the methyl ethyl ketone is 0.4 parts by weight or more and 40 parts by weight or less, when the mixed solvent contains the methyl propyl ketone, the content of the methyl propyl ketone is 0.4 parts by weight or more and 40 parts by weight or less, and when the mixed solvent contains the methyl isobutyl ketone, the content of the methyl isobutyl ketone is 0.4 parts by weight or more and 40 parts by weight or less.

[0061] <5>

[0062] like <1> to <4> The resin composition for ceramic green sheets according to any one of the above, wherein the mixed solvent further contains toluene.

[0063] <6>

[0064] like <1> to <4> The resin composition for ceramic green sheets according to any one of the above, wherein the mixed solvent does not contain toluene.

[0065] <7>

[0066] A method for manufacturing a ceramic green sheet, comprising: <1> to <6> A step of forming the resin composition for ceramic green sheets according to any one of items into a sheet shape.

[0067] <8>

[0068] A method for manufacturing a laminated ceramic electronic component, comprising the following steps:

[0069] By <1> to <6> Forming the ceramic green sheet resin composition as described in any one of the above into a sheet to produce a ceramic green sheet;

[0070] forming an internal electrode pattern on the ceramic green sheet;

[0071] Manufacturing a laminate by laminating a plurality of the ceramic green sheets on which the internal electrode patterns are formed; and

[0072] By firing the above-mentioned laminated body, a ceramic sintered body having a structure in which internal electrode layers are laminated with ceramic layers interposed therebetween is produced.

[0073] Example

[0074] Examples are shown below that more specifically disclose the resin composition for ceramic green sheets, the method for manufacturing ceramic green sheets, and the method for manufacturing multilayer ceramic electronic components of the present invention. It should be noted that the present invention is not limited to these examples.

[0075] (Example 1)

[0076] [Preparation of ceramic slurry]

[0077] 4 parts by weight of polyvinyl butyral (PVB) as an adhesive and 64 parts by weight of a mixed solvent of methylcyclohexane / ethanol as an organic solvent were mixed with 32 parts by weight of a ceramic powder (particle size in terms of specific surface area (SSA): 0.3 μm) mainly composed of barium titanate, thereby preparing a ceramic slurry (resin composition for ceramic green sheets) in which the ceramic powder was dispersed.

[0078] For polyvinyl butyral, polyvinyl butyral having a polymerization degree of 1700 and a hydroxyl group amount of 34 mol% was used. For the organic solvent, the composition ratio (weight ratio) was set to methylcyclohexane / ethanol = 50 / 50. The dispersion of the ceramic powder was carried out by mixing and pulverizing using a bead mill. In order to prevent foreign substances from being mixed into the sample, the disperser and the medium were cleaned with the same mixed solvent as above before and after use.

[0079] [Production of ceramic green sheet]

[0080] A ceramic green sheet having a thickness of 1 μm was produced from the prepared ceramic slurry using a forming machine.

[0081] [Production of multilayer ceramic capacitor]

[0082] A Ni paste containing an organic binder was screen-printed onto the obtained ceramic green sheet and then dried, thereby forming an internal electrode pattern. Regarding the thickness of the internal electrode pattern, it was adjusted so that the thickness of the dried coating film became 0.8 μm. Next, 300 ceramic green sheets formed with the internal electrode pattern were laminated to form an internal electrode holding layer, and 20 plain (Japanese: 無地) ceramic green sheets not formed with the internal electrode pattern were laminated on the front and back surfaces thereof, respectively, to form a protective layer.

[0083] After performing a debinding treatment and a firing treatment on the laminate including the internal electrode holding layer and the protective layer having the above structure, external electrodes were formed at both ends of the laminate. Through the above operations, a multilayer ceramic capacitor was produced as a multilayer ceramic electronic component.

[0084] The obtained ceramic green sheet and multilayer ceramic capacitor were evaluated as follows.

[0085] [Sheet surface roughness]

[0086] The surface roughness Ra of the ceramic green sheet was measured using an optical interference shape measuring instrument Zygo New View 7300 manufactured by Canon Marketing Japan Inc.

[0087] [Sheet density]

[0088] Five ceramic green sheets were punched out in a size of 5 cm×8 cm square, and the weight and thickness of each were measured to calculate the sheet density.

[0089] [Short Circuit]

[0090] Using a tester 4278A manufactured by Yokogawa Hewlett-Packard Company, 100 samples (laminated ceramic capacitors) were evaluated for short circuit under the conditions of 25° C., 120 Hz, and 1.0 V.

[0091] [Construction defects]

[0092] Figure 3 This is a cross-sectional view schematically showing an example of a structural defect in which a void is generated at the boundary between the end of the internal electrode layer and the ceramic layer. Figure 4 This is a cross-sectional view schematically showing an example of a structural defect in which an internal electrode layer is peeled off from a ceramic layer.

[0093] 100 chip components (laminated ceramic capacitors) were cross-sectioned and ground to Figure 3 and Figure 4 As shown, evaluate whether there are structural defects inside. Figure 3 The gap shown or Figure 4 The peeling shown was counted as a structural defect.

[0094] Table 1 shows the evaluation results.

[0095] (Example 2)

[0096] After preparing ceramic slurry in the same manner as in Example 1, except that a mixed solvent of methylcyclohexane / ethanol was used as the organic solvent and the composition ratio (weight ratio) was 80 / 20, a ceramic green sheet and a laminated ceramic capacitor were produced. The obtained ceramic green sheet and laminated ceramic capacitor were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0097] (Example 3)

[0098] After preparing ceramic slurry in the same manner as in Example 1, except that a mixed solvent of methylcyclohexane / ethanol was used as the organic solvent and the composition ratio (weight ratio) was 20 / 80, a ceramic green sheet and a laminated ceramic capacitor were produced. The obtained ceramic green sheet and laminated ceramic capacitor were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0099] (Example 4)

[0100] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / isopropyl alcohol (IPA) was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 20. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0101] (Example 5)

[0102] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / methyl ethyl ketone (MEK) was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 20. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0103] (Example 6)

[0104] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / methyl propyl ketone (MPK) was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 20. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0105] (Example 7)

[0106] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / methyl isobutyl ketone (MIBK) was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 20. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0107] (Example 8)

[0108] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 0.4 / 2. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0109] (Example 9)

[0110] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 80 / 20 / 6 / 0.4. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0111] (Example 10)

[0112] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 6 / 10. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0113] (Example 11)

[0114] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 6 / 20. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0115] (Example 12)

[0116] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 6 / 30. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0117] (Example 13)

[0118] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 6 / 40. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0119] (Example 14)

[0120] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 40 / 1. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0121] (Example 15)

[0122] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 70 / 30 / 4 / 1. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0123] (Example 16)

[0124] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 60 / 40 / 5 / 1. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0125] (Example 17)

[0126] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 50 / 50 / 6 / 1. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0127] (Example 18)

[0128] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 40 / 60 / 7 / 1. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0129] (Example 19)

[0130] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 30 / 70 / 8 / 1. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0131] (Example 20)

[0132] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK was used as the organic solvent and the composition ratio (weight ratio) was 20 / 80 / 9 / 2. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0133] (Example 21)

[0134] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of methylcyclohexane / ethanol / IPA / MEK / toluene was used as the organic solvent and the composition ratio (weight ratio) was 29 / 71 / 8 / 1 / 35. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0135] (Comparative Example 1)

[0136] After preparing ceramic slurry in the same manner as in Example 1, ceramic green sheets and multilayer ceramic capacitors were produced, except that a mixed solvent of ethanol / IPA / MEK / toluene was used as the organic solvent and the composition ratio (weight ratio) was 50 / 6 / 1 / 50. The obtained ceramic green sheets and multilayer ceramic capacitors were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0137] [Table 1]

[0138]

[0139] According to Table 1, in Comparative Example 1, a multilayer ceramic capacitor having many internal structural defects was obtained.

[0140] On the other hand, in Example 1, a laminated ceramic capacitor having fewer internal structural defects was obtained compared with Comparative Example 1. This is considered to be the result of the effect of obtaining a low-density ceramic green sheet with high plasticity compared with Comparative Example 1.

[0141] In Examples 2 and 3, similarly to Example 1, a multilayer ceramic capacitor having fewer internal structural defects than Comparative Example 1 was obtained.

[0142] In Example 4, similarly to Example 1, a laminated ceramic capacitor having fewer internal structural defects than Comparative Example 1 was obtained. In addition, short circuits were reduced compared to Example 1. This is believed to be because the solubility of PVB was improved by adding IPA to the mixed solvent.

[0143] In Example 5, similarly to Example 1, a laminated ceramic capacitor having fewer internal structural defects than Comparative Example 1 was obtained. In addition, short circuits were reduced compared to Example 1. This is believed to be because the solubility of PVB was improved by adding MEK to the mixed solvent.

[0144] In Example 6, similarly to Example 1, a laminated ceramic capacitor having fewer internal structural defects than Comparative Example 1 was obtained. In addition, short circuits were reduced compared to Example 1. This is believed to be because the solubility of PVB was improved by adding MPK to the mixed solvent.

[0145] In Example 7, similarly to Example 1, a laminated ceramic capacitor having fewer internal structural defects than Comparative Example 1 was obtained. In addition, short circuits were reduced compared to Example 1. This is believed to be because the solubility of PVB was improved by adding MIBK to the mixed solvent.

[0146] In Example 8, similarly to Example 1, a laminated ceramic capacitor having fewer internal structural defects than Comparative Example 1 was obtained. In addition, short circuits were reduced compared to Example 1. This is believed to be because the solubility of PVB was improved by adding IPA and MEK to the mixed solvent.

[0147] In addition, in Examples 9 to 20, the same effects as those of Example 8 were obtained.

[0148] In Example 21, although the mixed solvent contained toluene, due to the presence of methylcyclohexane, a ceramic green sheet with a lower density than that of Comparative Example 1 was obtained, and a multilayer ceramic capacitor with fewer internal structural defects was obtained.

[0149] Description of Reference Numerals

[0150] 1: Multilayer ceramic capacitor

[0151] 10: Laminated body

[0152] 11: Ceramic layer

[0153] 12: Internal electrode layer

[0154] 13, 14: External electrodes

[0155] 15, 16: End faces of the laminate

[0156] 17: Internal electrode holding layer

[0157] 18, 19: Protective layer

Claims

1. A resin composition for ceramic green sheets, comprising ceramic powder, a binder and an organic solvent, The adhesive is polyvinyl butyral, The organic solvent is a mixed solvent containing methylcyclohexane and ethanol.

2. The resin composition for ceramic green sheets according to claim 1, wherein The mixed solvent further contains at least one solvent selected from the group consisting of isopropyl alcohol, methyl ethyl ketone, methyl propyl ketone and methyl isobutyl ketone.

3. The resin composition for ceramic green sheets according to claim 1 or 2, wherein The content of the methylcyclohexane is 20 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the total of the methylcyclohexane and the ethanol.

4. The resin composition for ceramic green sheets according to claim 2, wherein The content of the methylcyclohexane is 20 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the total of the methylcyclohexane and the ethanol, and when the mixed solvent contains the isopropyl alcohol, the content of the isopropyl alcohol is 0.4 parts by weight or more and 40 parts by weight or less, when the mixed solvent contains the methyl ethyl ketone, the content of the methyl ethyl ketone is 0.4 parts by weight or more and 40 parts by weight or less, when the mixed solvent contains the methyl propyl ketone, the content of the methyl propyl ketone is 0.4 parts by weight or more and 40 parts by weight or less, and when the mixed solvent contains the methyl isobutyl ketone, the content of the methyl isobutyl ketone is 0.4 parts by weight or more and 40 parts by weight or less.

5. The resin composition for ceramic green sheets according to any one of claims 1 to 4, wherein The mixed solvent further contains toluene.

6. The resin composition for ceramic green sheets according to any one of claims 1 to 4, wherein The mixed solvent does not contain toluene. 7 . A method for producing a ceramic green sheet, comprising the step of forming the resin composition for a ceramic green sheet according to claim 1 into a sheet shape.

8. A method for manufacturing a laminated ceramic electronic component, comprising the following steps: A ceramic green sheet is produced by forming the resin composition for a ceramic green sheet according to any one of claims 1 to 6 into a sheet shape; forming an internal electrode pattern on the ceramic green sheet; Manufacturing a laminate by laminating a plurality of the ceramic green sheets on which the internal electrode patterns are formed; and By firing the laminated body, a ceramic sintered body having a structure in which internal electrode layers are laminated with ceramic layers interposed therebetween is produced.

Citation Information

Patent Citations

  • Environment-friendly bonding agent for ceramic sheet tape casting and preparation method of bonding agent

    CN102795865A

  • Method for mfg. laminated ceramic electronic parts

    CN1435856A